The effects of season, habitat, hydroperiod and water chemistry on the distribution of turlough aquatic invertebrate communities - Porst, Gwendolin (University of Dublin, Trinity College, 2009)
The aim of this study was to investigate the effects of season, habitat, hydroperiod and water chemistry on the distribution of turlough aquatic invertebrate communities. Twenty-two turloughs, selected as representative of geographical distribution and hydrological conditions were included in the study. A comparative study of eight turloughs representing a nutrient gradient determined macroinvertebrate community distinctiveness in a stratified sampling design and related assemblage structures to environmental variables. Assessment of macroinvertebrate temporal and spatial variation was the objective of separate studies conducted in a subset of four turloughs, varying in hydrological and nutrient regimes. The influence of disturbance and habitat characteristics on macroinvertebrate community dynamics was tested. Across twenty-two turloughs macroinvertebrate and cladoceran zooplankton communities were analysed and their relation to varying trophic, hydrological and morphological regimes identified. For a comparative study of macroinvertebrates eight turloughs were selected to represent a gradient of total phosphorus (TP) concentrations. To allow comparability of turlough macroinvertebrate communities, samples were collected from one habitat type (submerged grassland) in April 2007 using a simple box sampler. Five replicates were collected in every turlough by rapidly lowering the box to the substratum and removing trapped organisms with a net. Community analysis identified highly distinct macroinvertebrate assemblages, indicating that a single or pooled sample can provide a reliable description of turlough macroinvertebrate communities. Hydroperiod influenced mean taxon richness and abundance of macroinvertebrates but no correlation was found between nutrient status and either mean taxon richness or abundance. In order to study temporal dynamics of macroinvertebrates in turloughs, littoral faunal samples were collected over a one to two year period in four turloughs with differing hydrological and nutrient regimes. Sampling was carried out using a standardised sampling approach. Five replicate samples were collected every month using a box sampler from the dominant turlough habitat, submerged grassland. Macroinvertebrate biodiversity and community structure varied monthly and interannually. A two-phased hydrocycle was identified with permanent residents dominating during the start of the hydrocycle, with an increase of ephemeral taxa over time. Disturbance, as demonstrated by short hydroperiod and high areal reduction rate had an important effect on macroinvertebrate community structure in turloughs, with high disturbance generally supporting lower faunal diversity. Influence of disturbance generally decreased over time leading to a stabilization of macroinvertebrate communities. For the study of spatial variation of macroinvertebrates in turloughs two habitats were sampled in two turloughs during sampling season 2006/2007 using a box sampler and five replicates were collected in each habitat. Within-habitat variability was assessed by collecting five replicate macroinvertebrate samples from four different submerged grassland habitat sites in four turloughs in sampling season 2007/2008 using the box sampler. While habitat specific preferences were found for some taxa of conservation concern variability of macroinvertebrates within turloughs was nevertheless identified to be smaller than among turloughs. Macroinvertebrate samples collected in any location of the dominant turlough habitat (submerged grassland) were identified as reliable indicators of ecological change of turloughs. A comparative study of macroinvertebrates and cladoceran zooplankton communities was conducted across twenty-two turloughs, representing a wide hydromorphological and geographical range. Macroinvertebrate samples were collected in November 2006 and April 2007 using a stratified sampling approach. All available habitats in a turlough were sampled proportional to their availability using sweeps with a standard FBA pond net. Three minute sampling time was subdivided proportionally to each habitat?s availability. Cladoceran zooplankton and separate chydorid samples were collected from twenty turloughs in April 2007 by horizontal hauls with a zooplankton net from the shore and a perspex tube, respectively. Varying associations of macroinvertebrate as well as zooplankton communities to environmental variables season, TP concentrations, number of habitats sampled and hydroperiod of turloughs were detected. Some macroinvertebrate orders and zooplankton species showed significant relationships with chemical descriptors of nutrient enrichment. Turlough macroinvertebrate communities are highly distinct and conducive to time and cost-effective monitoring. Collection of a single submerged grassland sample reduces inherent `noise? and is suited for the detection of pressure gradients. The number of habitats sampled should, however, depend on the objective of the sampling. Sampling for more holistic purposes should be carried out using a multi-habitat sampling approach to obtain a more comprehensive survey of turlough biodiversity. Season had an important influence on macroinvertebrate community structures. Turlough sampling regimes need a flexible approach with timing and frequency of sampling depending on sampling protocol objectives and should be geared towards the start of the flooding season and variable hydrocycles. Turloughs are inherently variable systems which might negate the development of simple type-specific reference conditions as required for lakes under the WFD.
PUBLISHED
Keywords: Zoology; Habitat; Turloughs